United States, Iñupiat girls standing on beach in Utqiaġvik - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1959)
Group of four natives standing near beach. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3